Proceso de atención de enfermería en gestante de 36 semanas con desprendimiento prematuro de placenta más óbito fetal. - Zambrano Gonzales, María De Los Ángeles (2024)
The development of this clinical case study based on the nursing care process in a 16-week pregnant woman with premature placental abruption plus fetal death who was received at the Martín Icaza Bustamante general hospital in the city of Babahoyo with a referral from the hospital. de Ricaurte, this patient was received with a diagnosis of maternal care for intrauterine death that was evaluated by the doctor on duty and upon arrival the patient showed abdominal-pelvic pain with contractile where it spreads through the lumbosacral area with mild intensity in Regarding the patient's care, the corresponding physical examination was carried out, the analysis of vital signs was carried out, as well as the proper nursing processes were carried out, where the corresponding medication was administered, given by the doctor on duty. In conclusion, various health factors were identified. risk related to placental complications and fetal death, among them high blood pressure, multiple pregnancy, history of previous undertakings and abortions, in addition to this knowledge, it is important to detect early and be able to implement strategies in the at-risk population.